The opportunity to save a life: A qualitative study of a point-of-care overdose education and naloxone distribution intervention. - Janet A Parsons; Benjamin Markowitz; Rekha Thomas; Kris Norris; Mercy Charles; Chantelle King; Kate Sellen; Douglas M Campbell; Pamela Leece; Michelle Klaiman; Leigh Chapman; Shaun Hopkins; et al. (PLoS ONE, 2025)
Canada's opioid crisis continues to escalate. Naloxone can effectively reverse the effects of opioid overdose. We planned a randomized trial on the effectiveness of a point-of-care overdose education and naloxone distribution (OEND) intervention on participants' performance in a simulated opioid overdose scenario. In preparation for the trial, we conducted a feasibility study which included a qualitative process evaluation aimed at eliciting participants' perspectives of the study's OEND tool and procedures, and how their lived experiences of the opioid crisis intersected with their experiences of the study. Twenty-three participants were interviewed, including people with lived experiences of opioid use or overdose, and people living in neighbourhoods or working in services where they were likely to encounter overdose. Thematic analysis of interview transcripts was informed by stigma theory. Participants' accounts depicted challenges faced by people who take opioids in their everyday lives, deep losses experienced, negative attitudes encountered, and systemic barriers to care. Participation in the study itself was portrayed as meaningful. We explored participants' experiences through three key themes: (1) who were the participants - describing their experiences related to opioid overdose, opioid use and attendant stigma; (2) why did they participate - recounting their motivations to join the study; and (3) what they thought about study processes - reflecting on the OEND materials and study procedures. Accounts revealed a sense of agency as participants confronted the opioid crisis. Our results demonstrate that people experiencing opioid use and overdose and people who care about them are eager and willing to be approached about research at point of care; participants were eager to learn overdose prevention skills and to return for follow-up study sessions. They recounted a range of motivations for participating, the most important of which is the opportunity to actively intervene, save lives and raise awareness. Trial Registration: ClinicalTrials.gov registry (NCT03821649).